Subspecies and Distribution. L. t. timidus Linnaeus, 1758 — Scandinavia S to 59° N, N Russia (S to 57° N to 58° N) to E of Ural Mts, Estonia, perhaps Poland, and Altai and Beita Mts in N Xinjiang (China); from Sweden extending in hybrid zones with the subspecies sylvaticus to S coast of Norway and W Latvia. L. t. abet Kuroda, 1938 — Kurile Is (Russia). L. t. ainu Barrett-Hamilton, 1900 — Hokkaido (Japan). L. t. begitschevi Koljuschev, 1936 — Taimyr Peninsula (Russia). L. t. gichiganus J. A. Allen, 1903 — C Yakutia, Kamchatka and Okhotsk Sea coast (Russia). L. t. hibernicus Bell, 1837 — Ireland. L. t. kolymensis Ognev, 1922 — NE Siberia (Russia). L. t. kozhevnikovi Ognev, 1929 — C Russia from 57° to 58°N, whereit intergrades with the nomonotypical timidus S to 53° N. The W boundary is unclear. L. t. lugubris Kastschenko, 1899 — Siberian Altai Mts (Russia). L. t. mordeni Goodwin, 1933 — Russian Far East (Ussuri Valley and lower and middle Amur River) and Heilongjiang (China). L. t. ori Kuroda, 1928 — Sakhalin (Russia). L. t. scoticus Hilzheimer, 1906 — Scotland. L. t. sibiricorumJohansen, 1923 — W & SW Siberia (Russia), N Kazakhstan, and Tacheng Mts in N Xinjiang (China). L. t. sylvaticus Nilsson, 1831 —S Sweden, extending in hybrid zones with nominotypical timidus to S coast of Norway and W Latvia. L. t. transbaikalicus Ognev, 1929 — Trans-Baikal region in E Siberia (Russia) and E Inner Mongolia (= Nei Mongol, China). L. t. varronis Miller, 1901 — at high altitudes in the Alps, C Europe. in Leporidae - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
Subspecies and Distribution. L. t. timidus Linnaeus, 1758 — Scandinavia S to 59° N, N Russia (S to 57° N to 58° N) to E of Ural Mts, Estonia, perhaps Poland, and Altai and Beita Mts in N Xinjiang (China); from Sweden extending in hybrid zones with the subspecies sylvaticus to S coast of Norway and W Latvia. L. t. abet Kuroda, 1938 — Kurile Is (Russia). L. t. ainu Barrett-Hamilton, 1900 — Hokkaido (Japan). L. t. begitschevi Koljuschev, 1936 — Taimyr Peninsula (Russia). L. t. gichiganus J. A. Allen, 1903 — C Yakutia, Kamchatka and Okhotsk Sea coast (Russia). L. t. hibernicus Bell, 1837 — Ireland. L. t. kolymensis Ognev, 1922 — NE Siberia (Russia). L. t. kozhevnikovi Ognev, 1929 — C Russia from 57° to 58°N, whereit intergrades with the nomonotypical timidus S to 53° N. The W boundary is unclear. L. t. lugubris Kastschenko, 1899 — Siberian Altai Mts (Russia). L. t. mordeni Goodwin, 1933 — Russian Far East (Ussuri Valley and lower and middle Amur River) and Heilongjiang (China). L. t. ori Kuroda, 1928 — Sakhalin (Russia). L. t. scoticus Hilzheimer, 1906 — Scotland. L. t. sibiricorumJohansen, 1923 — W & SW Siberia (Russia), N Kazakhstan, and Tacheng Mts in N Xinjiang (China). L. t. sylvaticus Nilsson, 1831 —S Sweden, extending in hybrid zones with nominotypical timidus to S coast of Norway and W Latvia. L. t. transbaikalicus Ognev, 1929 — Trans-Baikal region in E Siberia (Russia) and E Inner Mongolia (= Nei Mongol, China). L. t. varronis Miller, 1901 — at high altitudes in the Alps, C Europe. Published as part of Don E. Wilson, Thomas E. Lacher, Jr & Russell A. Mittermeier, 2016, Leporidae, pp. 107-148 in Handbook of the Mammals of the World – Volume 6 Lagomorphs and Rodents I, Barcelona :Lynx Edicions on page 145, DOI: 10.5281/zenodo.6625539